2006
DOI: 10.1136/ard.2005.044784
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lymphoma in a large primary care derived cohort of cases of inflammatory polyarthritis

Abstract: There was a doubling in risk of lymphoma in new onset cases of inflammatory polyarthritis. Patients with the most severe disease were twice as likely as other patients to develop lymphoma. These results need to be taken into account when considering reported increased risks of lymphoma compared to background population risk in users of new biological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
10

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 27 publications
4
83
1
10
Order By: Relevance
“…10,11,38 However, a moderately increased NHL risk was observed among RA patients treated with corticosteroids or immunosuppressants, supporting a gradient in risk by treatment or disease severity. 38 In most participating studies, the prevalence of RA reported by the controls was higher than expected, 39 which could reflect a degree of misclassification with other joint or connective tissue disorders.…”
Section: Autoimmune Disorders and Lymphoma Subtypes 4035mentioning
confidence: 98%
See 1 more Smart Citation
“…10,11,38 However, a moderately increased NHL risk was observed among RA patients treated with corticosteroids or immunosuppressants, supporting a gradient in risk by treatment or disease severity. 38 In most participating studies, the prevalence of RA reported by the controls was higher than expected, 39 which could reflect a degree of misclassification with other joint or connective tissue disorders.…”
Section: Autoimmune Disorders and Lymphoma Subtypes 4035mentioning
confidence: 98%
“…In rheumatoid arthritis (RA) 10,11 and systemic lupus erythematosus (SLE), 12 an increased risk of malignant lymphomas has been described repeatedly, whereas the evidence is less consistent for other inflammatory disorders that display autoimmune phenomena, such as psoriasis, 13 inflammatory bowel disorders, 14 and sarcoidosis. 15 Discrepant results between studies may be the result of differences in study size and design and of differences in composition of lymphoma subtypes studied and failure to disentangle subtype-specific associations.…”
Section: Introductionmentioning
confidence: 99%
“…And how would chronic inflammation, elicited by any instigator, increase the risk of infection acquisition in the host (5,6)? Finally, there is now good evidence that patients with RA have a 2-fold increased risk of developing lymphoma (7,8). Specifically, patients are alerted to an increased risk of lymphoma when considering treatment with a tumor necrosis factor ␣ (TNF␣) blockade agent, but it is difficult to dissect the spontaneous risk from treatment-induced risk (9).…”
mentioning
confidence: 99%
“…Имеющиеся разрозненные данные по долгосрочному наблюдению пациентов с ЮИА в соответствии с клиниче-ским опытом не обнаруживают нарастания базального уров-ня злокачественных новообразований у пациентов с ЮИА, что было найдено у взрослых пациентов с РА [132][133][134][135][136]. Наиболее часто из опухолей наблюдалась лимфома (50%): 14 -неходжкинская или ходжкинская лимфома, 10 -гепатолиенальная Т-клеточная лимфома (см.…”
Section: клинические исследования ритуксимабаunclassified